The Dynamics of Good Governance During A Transition Period: An Analysis of the Performance and Authority of the Acting Head of the Jakarta Capital Region - Jenius Hakim Simanjuntak; Sidik Pramono (Eduvest - Journal of Universal Studies, 2026)
The end of the definitive regional head's term of office in the Special Capital Region (DKI) of Jakarta has triggered a vacuum of power in the provincial government's leadership. To fill this power vacuum, an Acting Regional Head (Pj. Gubernur) was appointed to ensure the continuity of public services and the implementation of ongoing policies in the Province of DKI Jakarta. The difference in the selection mechanisms between the definitive regional head (direct election) and the acting regional head (appointment by the Minister of Home Affairs) has raised concerns among various stakeholders regarding whether the implemented policies under the acting leadership have had positive impacts and adhered to the principles of good governance during the acting period. Therefore, a further analysis is required to assess the performance of the Acting Regional Head of DKI Jakarta in exercising the authority granted throughout his tenure. Using a descriptive-qualitative approach with literature study and document analysis, this research evaluates performance through the lens of good governance principles: properness, transparency, effectiveness, and accountability. Based on the analysis, there are notable performance differences between the acting and definitive regional heads, influenced by variations in the scope of authority, as well as internal and external factors within the Provincial Government of DKI Jakarta. The findings indicate that while the Acting Regional Head successfully maintained bureaucratic stability and policy continuity, significant gaps remain in transparency and public participation due to the absence of direct electoral legitimacy and limited strategic authority.